2007
DOI: 10.1007/s00125-007-0681-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and risk of endometrial cancer: a meta-analysis

Abstract: Aims/hypothesis Diabetes has been associated with a statistically significantly increased risk of endometrial cancer in most, but not all studies. To provide a quantitative assessment of the association between diabetes and risk of endometrial cancer, we conducted a meta-analysis of casecontrol studies and cohort studies. Subjects and methods We identified studies by a literature search of PubMed and Embase through to January 2007 and by searching the reference lists of relevant articles. Summary relative risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
295
5
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(320 citation statements)
references
References 61 publications
10
295
5
10
Order By: Relevance
“…Numerous epidemiological studies have identified associations between diabetes and several types of cancer in various populations [9][10][11][12][13][14][15][16][17][18][19] (Table 2). While the literature indicates a strong and consistent increased risk of cancer in people with type 2 diabetes, the strength of association depends on the specific cancer site.…”
Section: Epidemiology Of Diabetes and Cancer Incidencementioning
confidence: 99%
“…Numerous epidemiological studies have identified associations between diabetes and several types of cancer in various populations [9][10][11][12][13][14][15][16][17][18][19] (Table 2). While the literature indicates a strong and consistent increased risk of cancer in people with type 2 diabetes, the strength of association depends on the specific cancer site.…”
Section: Epidemiology Of Diabetes and Cancer Incidencementioning
confidence: 99%
“…The effects of high serum glucose and hyperinsulinaemia, hall marks of type 2 diabetes, are well known and are associated with a wide range of chronic diseases of Western civilisation (Kuusisto et al 1997;Xu et al 2004;Friberg et al 2007;Xue and Michels 2007;Johnson et al 2009;Orgel and Mittelman 2013). High serum glucose is functionally related to the glycosylation of protein, which increases the rate of aging of tissues.…”
Section: Health Effects Of Fat As a Macronutrient And Energy Sourcementioning
confidence: 99%
“…Epidemiological studies have shown that diabetes [1][2][3][4][5][6][7] or certain treatments for diabetes may increase the risk [8][9][10] of developing cancer. Diabetes may also affect the treatment of cancer; some types of cancer are treated less aggressively in patients with diabetes than in patients without diabetes [11].…”
Section: Introductionmentioning
confidence: 99%